Degree of satisfaction with the incentives offered to high school principals from their point of view in Karak Governorate - Jordan - Al - Habashneh, Ismail Abdel Rahman (Arab Journal for Sciences and Research Publishing, 2017)
The goal of the current research was to investigate the degree of satisfaction with administrative work incentives According to the 3 sections material and no-material incentives and profession development incentives for school principals, based on social type, qualifications, job experience and educational district from secondary school principals' point of view at Al Karak province. The population of the study involved all of the (100) secondary school principals in Al Karak region for the academic year2015 /2016.Responded to study 97 principals (44 males and 53 females). The study instrument consisted of a questionnaires were designed to achieve the objectives of the study. The questionnaire survey to measure the degree of satisfaction with work incentives distributed over 3 sections. The findings of the research indicated that secondary school principals achieved great degree of satisfaction with work incentives in the first and second section respectively; material and non-material incentives. Also, the findings showed that school principals obtained an average or medium degree of satisfaction in professional development in the third section. This revealed that there were statistically no significant differences attributed to social type differentiation, qualification, experience and educational district. Finally, the study come out with a number of recommendations, these are; establishing an independent system for promotion and incentives consistent with the changeable economic, emphasizing the importance of material and non-material incentives and involving schools principals in particular the secondary school principals in making decision to achieve cooperation and job satisfaction in order to motivate them to work.
Keywords: Level of satisfaction; Incentives; High school principals